Analysis of stress state coefficient in the critical point during compression process of flat specimen by bowlerly dies - Vilotić, Dragiša (Journal of Production Engineering, 1984)
It is possible to determine workability diagram by means of deformations process in which stress and stain components are known. In this paper determination methodology of stress state and stress state coefficient 13" in the critical zone in compression of flat specimen by bowlerly dies is preaented. Relationship between factor and strain and other factors, was made too. Determination of stress component was made in the plane strain condition and other suposition by slab method. Relationship between stress state coefficient and strain shows that teh compression of flat specimen by bowlerly dies is very unmonotonous one.